Increased pollen flow counteracts fragmentation in a tropical dry forest: an example from Swietenia humilis Zuccarini. - White, G; Boshier, D; Powell, W (2002)
Habitat destruction and the resultant fragmentation of the remaining forest are a common phenomenon in the tropics. Most investigations emphasize the potential dangers of fragmentation in isolating patches of forest and exposing populations to loss of species diversity through founder effects, genetic drift, inbreeding, and restricted gene flow. However, a limited number of studies have shown that gene flow may be extensive in tropical trees, suggesting that it may occur between forest fragments and also "isolated" remnant trees. There is an urgent need to quantify pollen flow within and between forest fragments to test the veracity of such views and determine the genetic value of such fragments for in situ conservation. Microsatellite markers are used to genotype individuals of Swietenia humilis from a highly fragmented forest mosaic to directly quantify pollen-mediated gene flow. Distances of pollen flow more than 10 times greater than previously reported were detected. Our results show that some tropical angiosperm tree species may be much more adaptable and resilient to habitat destruction and fragmentation than previously considered. The description of many remnant trees as isolated or "living dead" may be more a conditioning of human perception than a true reflection of their potential conservation value.